(untitled) (Research, Society and Development, 2020)
Objective: This study compared low intensity laser therapy and dry needling, in the short and long term, in the treatment of myofascial pain, from pain to muscle palpation and in mandibular mobility. Methodology: This is a clinical trial in which 28 individuals were recruited to participate in the study. The patients were randomly assigned to two groups: GI (laser therapy) and Gll (dry needling). In GI there were 12 applications and in GII, three applications. Patients in both groups underwent nine evaluations (T0-T8). Return visits and new evaluations were carried out sixty days and 18 months after the end of the therapies in order to evaluate their efficacy and possible cumulative effects. To compare the groups in all parameters over time, ANOVA GLM and Multiple Comparison of Tukey were used with a significance level of 5% for all analyzes. Results: In general, the two therapies tested were effective for all parameters evaluated at T7 (2 months after T6). However, at T8, dry needling therapy was found to support the results compared to laser therapy. Conclusion: It is concluded that, although both therapies were effective, for immediate relief of symptoms of myofascial pain, dry needling was more efficient and lasting in the analyzed parameters.